The greatest show on earth: the evidence for evolution - Dawkins, Richard (United States : Paramount Pictures, United States : [Paramount Home Video, 2009)
The Ringling Brothers-Barnum and Bailey Circus provides the settings and co-stars of this look at life under the big tent, including the personal stories of the behind-the-scenes circus lives of lion tamers, circus flyers, acrobats, tightrope walkers, clowns, and others.
Copyright: Paramount Pictures Corp.; 1Apr52; LP1842.
Copyright notice on videodisc jacket: Paramount Pictures Corporation ; 1982.
Produced with the cooperation of Ringling Bros.-Barnum & Bailey Circus.
Possible videodisc reissue date from copyright notice on videodisc jacket.
Two videodiscs in one videodisc jacket.
Running time given as 149 minutes on videodisc jacket and as 153 minutes in Catalog of copyright entries : motion pictures, 1950-1959, p. 132.